Early dropout, earnings and skills in later life: evidence from Spain. - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (Taylor & Francis, 2023)
Most education systems have set a minimum age until which students must stay at school. In the case of Spain, students can drop out the same day they reach that age, even without finishing that academic year. In the present research work we intend to analyse the influence of early dropout on later life outcomes for the Spanish population, i.e. literacy and numerical skills and earnings. In order to do this, we employ PIAAC 2012 data and a fuzzy regression discontinuity design, focusing on a transition period between education laws: a first period without minimum dropout age and a second period (law approved in 1970) which obligated students to be at least 14 years-old to dropout. Our results show, for this particular cohort of the Spanish population, that dropping out is substantially negatively associated with literacy and numerical skills in around 1.5 standard deviations, while it did not influence future earnings.
https://openpolicyfinder.jisc.ac.uk/id/publication/6017
Keywords: Fracaso escolar; Lectura; Escritura; Aptitudes matemáticas; Salarios; Educación - Aspectos sociales; Educación - Modelos econométricos; Dropout; Literacy skills; Numerical skills; Earnings; Fuzzy regression discontinuity